Pelatihan dan Edukasi Pada Ibu Balita dalam Pencegahan Stunting di Desa Karang Intan 1 sebagai Area Lahan Basah Kalimantan Selatan - Agianto Agianto; Fujiati Fujiati; Roselina Panghiyangani; Nelly Al Audah; Arief Budiarto; Sukma Noor Akbar; Nanda Shaskia Larasaty; Puga Sharaz Wangi; Seri Wahyuni; Danny Indrawardhana; Dwi Purbayanti; Deby Kania Tri Putri; Nurul Hidayah; Muhammad Irwan Setiawan; Muhammad Fakhruddin Noor; Muhammad Iqbal; Ary Nugraha; Muhammad Ikhwan Rizki (Universitas Muhammadiyah Mataram, 2026)
Abstract: The prevalence of stunting in South Kalimantan remains high, requiring special attention in implementing more effective intervention programs. The purpose of community service activities is to increase knowledge and strengthen the active role of the community, especially mothers of toddlers, in preventing stunting and supporting the acceleration of reducing stunting prevalence. The method used was training and education for housewives in stunting prevention in Karang Intan Village. The target of the activity was 30 mothers with toddlers. The series of activities included a pre-test delivering educational materials on stunting, weighing practices, identifying stunting from body weight, and determining nutrition from simulations and practices. Interactive discussions and post-tests were conducted to evaluate the increase in knowledge of mothers of toddlers. The results of the activity showed a significant increase in knowledge, where at the pre-test stage, 86.6% were already in the good category, and after the intervention, all respondents (100%) were in the good category. Health education is effective in improving and strengthening the understanding of mothers of toddlers regarding stunting prevention.Abstrak: Prevalensi stunting di Kalimantan Selatan masih berada pada kategori tinggi, sehingga memerlukan perhatian khusus dalam implementasi program intervensi yang lebih efektif. Tujuan kegiatan pengabdian kepada masyarakat adalah untuk meningkatkan pengetahuan, dan memperkuat peran aktif masyarakat khususnya ibu balita dalam mencegah stunting dan mendukung percepatan penurunan prevalensi stunting. Metode yang digunakan adalah pelatihan dan edukasi pada ibu rumah tangga dalam pencegahan stunting di Desa Karang Intan. Sasaran kegiatan adalah 30 ibu yang memiliki balita. Rangkaian kegiatan berupa pre-test penyampaian materi edukasi tentang stunting, praktik penimbangan, identidfikasi stunting dari berat bada, penentuangizi dari simulasi dan praktik. Diskusi interaktif serta post-test untuk mengevaluasi peningkatan pengetahuan ibu Balita. Hasil kegiatan menunjukkan adanya peningkatan pengetahuan yang signifikan, dimana pada tahap pre-test sebesar 86,6% sudah berada pada kategori baik, dan setelah intervensi seluruh responden (100%) berada pada kategori baik. Edukasi kesehatan efektif dalam meningkatkan dan memperkuat pemahaman ibu balita terkait pencegahan stunting.